Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0081-001 International HVT/EAB/MS/1,437 29th August, 1939. Mr. L. W. Burge, Home Office (Aliens Department), Cleland House, Page Street, London, S.W.1. Dear Sir, SPANISH SEAMEN. Thank you for your letter of the 23rd instant enquiring as to the possibility of Spanish Seamen now in this country finding employment on British ships. This matter is receiving our attention and I will write to you further at a later date. Yours sincerely, Assistant Secretary 292/946/25a/81